Electronic Imaging & the Visual Arts. EVA 2016 Florence (11-12 May 2016) - Cappellini, Vito; DEL RE, ENRICO (Proceedings e report, 2016)
Information Technologies of interest for Culture Heritage are presented: multimedia systems, data-bases, data protection, access to digital content, Virtual Galleries. Particular reference is reserved to digital images (Electronic Imaging & the Visual Arts), regarding Cultural Institutions (Museums, Libraries, Palace - Monuments, Archaeological Sites). The International Conference includes the following Sessions: Strategic Issues; New Science and Culture Developments & Applications; New Technical Developments and Applications; Museums - Virtual Galleries and Related Initiatives; Access to the Culture Information. An International Forum on "Culture & Technology" is enclosed. One Workshop regards: Innovation and Enterprise.